2008
DOI: 10.1192/bjp.bp.106.033597
|View full text |Cite
|
Sign up to set email alerts
|

Out-patient psychotherapy for borderline personality disorder: Cost-effectiveness of schema-focused therapy v. transference-focused psychotherapy

Abstract: Despite the initial slight disadvantage in QALYs, there is a high probability that compared with TFP, SFT is a cost-effective treatment for borderline personality disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 29 publications
1
119
2
4
Order By: Relevance
“…Schema-Focused Therapy (SFT) has shown particular promise as a comprehensive treatment for BPD with the goal of complete recovery in a large, well-designed clinical trial of individual psychotherapy twice weekly for three years or less in the Netherlands (Giesen-Bloo et al, 2006). In addition, cost-effectiveness for SFT was demonstrated (Van Asselt et al, 2008). An independent small-scale Norwegian case series study reported similar effectiveness of individual SFT (Nordahl & Nysaeter, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…Schema-Focused Therapy (SFT) has shown particular promise as a comprehensive treatment for BPD with the goal of complete recovery in a large, well-designed clinical trial of individual psychotherapy twice weekly for three years or less in the Netherlands (Giesen-Bloo et al, 2006). In addition, cost-effectiveness for SFT was demonstrated (Van Asselt et al, 2008). An independent small-scale Norwegian case series study reported similar effectiveness of individual SFT (Nordahl & Nysaeter, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…Finally, the cognitive schema perspective suggests that it might be interesting to investigate the value of not only classic CBT (cognitive behavioural therapy) techniques such as challenging cognitions and emotions, but also of techniques adopted from schema-focused therapy (Van Asselt et al 2008;Young et al, 2003), compassionate mind training (Gilbert & Procter, 2006) and emotionfocused therapy (Greenberg, 2004). One example is the 'limited re-parenting' technique.…”
Section: Discussionmentioning
confidence: 97%
“…The developments in effective therapies for Personality Disorders (Bernstein, Arntz, & Vos, 2007;Farrell, Shaw, & Webber, 2009;Nadort et al, 2009;van Asselt et al, 2008) suggest that psychotherapeutic interventions reducing factors underlying antisocial behavior should be a key area of investment when dealing with personality-disordered inmates (Gilbert & Daffern, 2011;Kjelsberg et al, 2006). Similarly to what is done in the case of substance dependence/abuse, differential treatment for subjects with severe personality pathology should be provided to ensure adequate treatment and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%